Teacher Workload and Implementation of Digital Literacy Programme in Public Primary Schools in Kitui West Subcounty, Kenya - Kitonga, Muthengi Brian; Kalai, Jeremiah; Njagi, Lucy (Journal of Education and Practice, 2024)
Purpose: The aim of the study was to investigate the influence of teacher workload on implementation of digital literacy programme in Kitui County, Kenya. The research question addressed the following key items: The status of teacher workload among primary school teachers, activities that limit teachers from integrating ICT in learning and the challenges that teachers faced while preparing for ICT classes and the mitigation measures that may help in ensuring teachers integrate ICT fully in teaching and learning. Methodology: The study used descriptive survey design were both qualitative and quantitative data were analysed. Inferential statistics was used to determine the influence of independent variable on the dependent variable Statistical Package for Social Sciences was used to analyse data which was presented using two sample t-test tables and percentages. The target population for the study was all 80 head of institutions, 710 teachers and 1550 Grade 1 pupils from all 80 primary schools in Kitui West Subcounty. Simple random sampling technique was used to select the sample size of 24 headteachers, 213 teachers, and 155 Grade 1 pupils. Data were collected using questionnaire for teachers, interview guides for headteachers and focus discussion guides were used for pupils. Findings: The finding indicated that there was a positive coefficient of 0.611 was realized on teacher training, hence teacher training had influence on execution of the digital programme. On teacher workload, a difference of 2.1666 was recorded implying that teacher workload was significantly less in schools where teachers were frequently using ICT devices Unique Contribution to Theory, Policy and Practice: The recommendations of the study were; the Teachers Service Commission should recruit additional teachers to address the high workload and create more time for digital utilization in classroom teaching. Moreover, there is need to have proper planning on the time allocated for an ICT class so that teachers deliver adequately during the lessons.